Eye Care Interventions in Critical/Surgical Patients in the Prone Position: Scoping Review - Ana Clara Dantas; Marília Lopes Costa; Amanda Barbosa da Silva; Bárbara Ebilizarda Coutinho Borges; Jéssica Naiara de Medeiros Araújo; Allyne Fortes Vitor (Universidad de La Sabana, 2022)
Objectives: This study aimed to map evidence of eye care interventions in managing critical or surgical patients submitted to prone positions. Materials and method: This scoping review was prepared according to the Joanna Briggs Institute's methodology, following the PRISMA-ScR criteria. A search was conducted from July to August 2020 in the SCOPUS, Web of Science, Science Direct, PubMed Central, CINAHL, and COCHRANE databases. The following research question was delimited: "What are the strategies and interventions used for eye care in the management of critical patients or surgical patients submitted to the prone position?" The sample consisted of 24 studies after applying the inclusion and exclusion criteria. Results: Eye care interventions in managing critical/surgical patients submitted to the prone position were eye examination, use of lubricants/specific ophthalmic solution, reverse Trendelenburg positioning, and protection with adhesive tape. Conclusions: This review allowed the understanding of eye care for critical/surgical patients in a prone position. Among the care presented, a large part is related to nursing since it is closer to patient care. The findings emphasize the need to implement patient safety policies with eye care as a priority.